ADVERSITY QUOTIENT PADA PERAWAT RUMAH DI RUMAH SAKIT DITINJAU DARI FAKTOR DEMOGRAFIS: ADVERSITY QUOTIENT OF HOSPITAL NURSES BASED ON DEMOGRAPHIC FACTORS - Rut Marselia; Maria Estela Karolina (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
Introduction The role of nurses as health care providers in hospitals which amounted to 40% -60% must provide prime, efficient, effective, and productive services care for patients / communities. Nurses are the largest group of health care providers in hospitals who work on nearly 90% of health care through nursing care and greatly affect patient outcomes. The duties and responsibilities of the nurses are very high in work such as, high job demands, responsible for the safety of patient's life, strict work schedule, heterogeneity of personnel, dependence on work, competitive culture in the hospital, and peer pressure. Given the difficulties, it’s crucial to find out the importance of knowing the adversity quotient of nursesin order to see how far the nurse faces difficulties and job barriers in terms of demographic factors. Objective This study aims to determine the description of adversity quotient based on demographic factors.Method This research used quantitative research method with descriptive approach. The sample was taken using non probability sampling technique by purposive sampling The research took place at Mental Hospital of Jambi Province, St.Theresia Hospital and Ahmad Ripin Muaro Jambi Hospital. Subjects in this study were nurses that fulfil the criteria: have work experience in the hospital over>1 year and have nurse educational background. The total number of subjects in this study was 192 subjects. This study used adversity quotient scale as a measuring tool.Results The results showed that the level of adversity quotient of 126 nurses (65.6%) in hospital was in the moderate category. There was a relationship ofadversity quotient with age (p = 0,006) and number of dependants (p = 0,046).Keywords: Adversity Quotient, employment, nursed. ABSTRAK Pendahuluan Peran perawat sebagai penyedia layanan kesehatan di rumah sakit yang berjumlah 40% -60% harus memberikan perawatan layanan prima, efisien, efektif, dan produktif bagi pasien masyarakat. Perawat adalah kelompok penyedia layanan kesehatan terbesar di rumah sakit yang menangani hampir 90% perawatan kesehatan melalui perawatan dan sangat mempengaruhi hasil pasien. Tugas dan tanggung jawab perawat sangat tinggi dalam pekerjaan seperti, tuntutan pekerjaan yang tinggi, bertanggung jawab atas keselamatan hidup pasien, jadwal kerja yang ketat, heterogenitas personel, ketergantungan pada pekerjaan, budaya kompetitif di rumah sakit, dan tekanan teman sebaya. Mengingat kesulitannya, penting untuk mengetahui pentingnya mengetahui tingkat kesulitan perawat dalam rangka untuk melihat seberapa jauh perawat menghadapi kesulitan dan hambatan pekerjaan dalam hal faktor demografis. Tujuan Penelitian ini bertujuan untuk menentukan deskripsi tingkat kesulitan berdasarkan faktor-faktor demografis. Metode Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan deskriptif. Sampel diambil dengan menggunakan teknik non probability sampling dengan purposive sampling. Penelitian ini dilakukan di Rumah Sakit Jiwa Provinsi Jambi, Rumah Sakit St.Theresia dan Rumah Sakit Ahmad Ripin Muaro Jambi. Subjek dalam penelitian ini adalah perawat yang memenuhi kriteria: memiliki pengalaman kerja di rumah sakit selama> 1 tahun dan memiliki latar belakang pendidikan perawat. Total jumlah subjek dalam penelitian ini adalah 192 subjek. Penelitian ini menggunakan skala adversity quotient sebagai alat ukur. Hasil Hasil penelitian menunjukkan bahwa tingkat adversity quotient dari 126 perawat (65,6%) di rumah sakit berada dalam kategori sedang. Ada hubungan kecerdasan adversitas dengan usia (p = 0,006) dan jumlah tanggungan (p = 0,046). Kata kunci Adversity Quotient, pekerjaan, dirawat.